2003
DOI: 10.1177/0193945902238838
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Health in Older Thai Persons in the United States

Abstract: Health and spiritual phenomena are viewed differently depending on the cultural perspective. This study describes spirituality as perceived and experienced by older Thai persons. Specific aims were to describe how spirituality helped older Thai persons maintain their health and to describe what they valued most as they aged. A qualitative, descriptive study informed by ethnographic methods was utilized. The sample included 9 older Thai persons from an urban U.S. community. Data were generated using ethnographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Some variation may be explained by the younger age of Kwong's participants. In a similar vein, Pincharoen and Congdon (2003) found that participants enjoyed talking about things for which they felt valued and respected by their communities. Domestic and social standing may well be accrued through the ritualistic value of Songkran food events (Hayami, 1998;Moore, 1996).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Some variation may be explained by the younger age of Kwong's participants. In a similar vein, Pincharoen and Congdon (2003) found that participants enjoyed talking about things for which they felt valued and respected by their communities. Domestic and social standing may well be accrued through the ritualistic value of Songkran food events (Hayami, 1998;Moore, 1996).…”
Section: Discussionmentioning
confidence: 84%
“…Personal faith was seen to contribute positively to quality of life for Thai women living with diabetes (Puavilai & Stuifbergen, 2000). As well, older Thai men and women living in the United States found going to the temple improved healthfulness and happiness through finding comfort and peace, and harmonising the body and mind (Pincharoen & Congdon, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the respondents' purposes for engaging in activities were altruistic in nature and rewarded them with nothing more but a sense of self-worth and usefulness. According to Pincharoen and Congdon (2003), aging is a time to cultivate a conscious candor within the self and the body, thus allowing one to develop a stronger spirit and relationship with the body as it declines. In the same light, the elderly respondents recognized an ardent force within themselves that propelled them toward spirituality and religious activity-now more than ever.…”
Section: Living Disposition: One Step Forwardmentioning
confidence: 99%
“…In addition, post-positivism, pragmatism and advocacy have been identified as approaches between these two extremes (Jennings, 2010;Pincharoen & Congdon, 2003;Teddlie & Tashakkori, 2003).…”
Section: Constructivism Paradigmmentioning
confidence: 99%